A controlled trial of a low sodium, low fat, high fibre diet in treated hypertensive patients: the efficacy of multiple dietary intervention. Issue 778 (August 1990) - Little, P.; Girling, G.; Hasler, A.; Trafford, A.; Craven, A.
Abstract : An 8-week combination low sodium, low fat, high fibre diet was compared to the individual components of this diet in a controlled trial using 193 patients already on treatment for essential hypertension. No significant changes were observed in the high fibre group. The low sodium group showed a decrease in systolic blood pressure which was close to significance. The low fat group showed a small but significant decrease in seated diastolic blood pressure and weight. The combination group showed larger and highly significant decreases in seated and standing systolic blood pressures, seated diastolic blood pressure and weight, as well as a significant reduction in standing diastolic blood pressure. We conclude that multiple dietary intervention in this case in the form of a low sodium, low fat, high fibre diet, is more effective than any single dietary intervention and is useful in patients already on medication.